Inter-district rice water productivity differences in Bangladesh: an empirical exploration and implications - Alauddin, M.; Sharma, Bharat R. (Elsevier, 2013)
While the bulk of research on crop water productivity (WP) focuses on static cross-section analysis, this research provides a spatio-temporal perspective. It estimates rice crop WP for 21 Bangladesh districts for 37 years; exploresWP variations among districts; and investigates causality involving WP, intensification and technological variables; and groundwater irrigation and depth. It breaks new grounds by probing these significant but unexplored issues. Technological diffusion was the key factor explaining inter-district WP differences. The impact of agricultural intensification on rabi (dry season) and kharif (wet season) crop WPs was positive and negative respectively. Dummy variables typifying policy transition negatively impacted on WPs for both kharif and overall crops. While rabi and kharif rice WPs grew with time, overall crop WP recorded the strongest growth. Rabi and overall WPs were lower in salinity- and drought-prone districts covering 33% of Bangladesh's net cropped area (NCA). In 90% of Bangladesh's NCA districts, technological diffusion caused WP. Causality existed between groundwater irrigation and depth in 60% NCA. Despite significant potential to increaseWP, increasing dependence on groundwater appears unsustainable. Widespread diffusion of HYVs in the kharif season, and development of salinity and drought-tolerant rice varieties could go a long way in sustaining rice WP.